Vibration and Damping Analysis of Composite Fiber Reinforced Wind Blade with Viscoelastic Damping Control - Tai-Hong Cheng; Ming Ren; Zhen-Zhe Li; Yun-De Shen (Advances in Materials Science and Engineering)
Composite materials are increasingly used in wind blade because of their superior mechanical properties such as high strength-to-weight and stiffness-to-weight ratio. This paper presents vibration and damping analysis of fiberreinforced composite wind turbine blade with viscoelastic damping treatment. The finite element method based on full layerwise displacement theory was employed to analyze the damping, natural frequency, and modal loss factor of composite shell structure. The lamination angle was considered in mathematical modeling. The curved geometry, transverse shear, and normal strains were exactly considered in present layerwise shell model, which can depict the zig-zag in-plane and out-of-plane displacements. The frequency response functions of curved composite shell structure and wind blade were calculated. The results show that the damping ratio of viscoelastic layer is found to be very sensitive to determination of magnitude of composite structures. The frequency response functions with variety of thickness of damping layer were investigated. Moreover, the natural frequency, modal loss factor, and mode shapes of composite fiber reinforced wind blade with viscoelastic damping control were calculated.